Differential impact of mechanical unloading on structural and nonstructural components of the extracellular matrix in advanced human heart failure - Sakamuri, Siva S.V.P.; Takawale, Abhijit; Basu, Ratnadeep; Fedak, Paul W.M.; Freed, Darren; Sergi, Consolato; Oudit, Gavin Y.; Kassiri, Zamaneh (Translational research : the journal of laboratory and clinical medicine, 2016)
Adverse remodeling of the extracellular matrix (ECM) is a significant characteristic of heart failure. Reverse remodeling of the fibrillar ECM secondary to mechanical unloading of the left ventricle (LV) by left ventricular assist device (LVAD) has been subject of intense investigation; however, little is known about the impacts on nonfibrillar ECM and matricellular proteins that also contribute to disease progression. Explanted failing hearts were procured from patients with nonischemic dilated cardiomyopathy (DCM) with or without LVAD support, and compared to nonfailing control hearts. LV free wall specimens were formalin-fixed, flash-frozen or optimum cutting temperature-mount frozen. Histologic and biochemical assessment of fibrillar ECM showed that LVAD support was associated with lower levels of insoluble collagen, collagen type I mRNA, and collagen I/III ratio compared with no-LVAD hearts. A disintegrin and Metalloproteinase with Thrombospondin Motifs-2 (ADAM-TS2), a procollagen endopeptidase, was reduced in no-LVAD but not in LVAD hearts. The rise in ECM proteolytic activities was significantly lower in LVAD hearts. Matrix metalloproteinases (MMP1, MMP2, MMP8, MMP13, and MT1-MMP/MMP14) were comparable between DCM hearts. Tissue inhibitor of metalloproteinase (TIMP)3 and TIMP4 messenger RNA and protein showed the greatest reduction in no-LVAD hearts. Basement membrane proteins exhibited less severe disarray of laminin and fibronectin-1 in LVAD-supported hearts. The rise in matricellular protein, osteopontin, was suppressed in LVAD hearts, whereas secreted protein, acidic, cysteine-rich (SPARC) levels was unaffected by LVAD. Mechanical unloading of the failing DCM hearts can restore the fibrillar ECM and the basement membrane, contributing toward improved clinical outcomes. However, persistent elevation of matricellular proteins such as SPARC could contribute to the relapse of failing hearts on removal of LVAD support.